A Russian View on Teaching Russian History in Canadian Universities - Avdeev, Victor (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
As a Russianist, I have always been interested in understanding the basic approaches in teaching Russian studies in the West. My intimate knowledge of the development of Western historiography — and its latest developments — can only clarify, though, some facets of my inquiry. In 2014, as a visiting professor of Russian history at Brock University, I had the chance to acquaint myself with essential principles, forms, and methods of teaching Russian history in Canada. I also appreciated the opportunity to find out the source of Canadian students’ interest in Russian history, their motivation, likes and dislikes in learning and researching it. Comparing Russian and Canadian ways of teaching Russian history and discussing the inconsistent views of Canadian students toward Russian history, I would like to define the most useful concepts and forms to assist in the learning of the Russian past in both our countries, despite current political troubles.